The role of Notch signaling in the mammalian ovary. Issue 6 (June 2017) - Vanorny, Dallas A; Mayo, Kelly E
Abstract : The Notch pathway is a contact-dependent, or juxtacrine, signaling system that is conserved in metazoan organisms and is important in many developmental processes. Recent investigations have demonstrated that the Notch pathway is active in both the embryonic and postnatal ovary and plays important roles in events including follicle assembly and growth, meiotic maturation, ovarian vasculogenesis and steroid hormone production. In mice, disruption of the Notch pathway results in ovarian pathologies affecting meiotic spindle assembly, follicle histogenesis, granulosa cell proliferation and survival, corpora luteal function and ovarian neovascularization. These aberrations result in abnormal folliculogenesis and reduced fertility. The knowledge of the cellular interactions facilitated by the Notch pathway is an important area for continuing research, and future studies are expected to enhance our understanding of ovarian function and provide critical insights for improving reproductive health. This review focuses on the expression of Notch pathway components in the ovary, and on the multiple functions of Notch signaling in follicle assembly, maturation and development. We focus on the mouse, where genetic investigations are possible, and relate this information to the human ovary.